Characterization of Common Carp Transcriptome: Sequencing, De Novo Assembly, Annotation and Comparative Genomics - Ji, Peifeng; Liu, Guiming; Xu, Jian; Wang, Xumin; Li, Jiongtang; Zhao, Zixia; Zhang, Xiaofeng; Zhang, Yan; Xu, Peng; Sun, Xiaowen (PLOS ONE, 2012)
Background Common carp (Cyprinus carpio) is one of the most important aquaculture species of Cyprinidae with an annual global production of 3.4 million tons, accounting for nearly 14% of the freshwater aquaculture production in the world. Due to the economical and ecological importance of common carp, genomic data are eagerly needed for genetic improvement purpose. However, there is still no sufficient transcriptome data available. The objective of the project is to sequence transcriptome deeply and provide well-assembled transcriptome sequences to common carp research community. Result Transcriptome sequencing of common carp was performed using Roche 454 platform. A total of 1,418,591 clean ESTs were collected and assembled into 36,811 cDNA contigs, with average length of 888 bp and N50 length of 1,002 bp. Annotation was performed and a total of 19,165 unique proteins were identified from assembled contigs. Gene ontology and KEGG analysis were performed and classified all contigs into functional categories for understanding gene functions and regulation pathways. Open Reading Frames (ORFs) were detected from 29,869 (81.1%) contigs with an average ORF length of 763 bp. From these contigs, 9,625 full-length cDNAs were identified with sequence length from 201 bp to 9,956 bp. Comparative analysis revealed that 27,693(75.2%) contigs have significant similarity to zebrafish Refseq proteins, and 24,371(66.2%), 24,501(66.5%) and 25,025(70.0%) to teraodon, medaka and three-spined stickleback refseq proteins. A total of 2,064 microsatellites were initially identified from 1,730 contigs, and 1,639 unique sequences had sufficient flanking sequences on both sides for primer design. Conclusion The transcriptome of common carp had been deep sequenced, de novo assembled and characterized, providing the valuable resource for better understanding of common carp genome. The transcriptome data will facilitate future functional studies on common carp genome, and gradually apply in breeding programs of common carp, as well as closely related other Cyprinids.